صورة الدّهر في شعر الموالي في العصر الأمويّ - يعقوب عبد الكريم; زهيرة بثينة (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
تتيح لنا النصوصُ الشعرية, بصورة عامة, فرصةَ اقتحام عالم الشاعر الخاص, ومقاربةَ واقعه, بفضل ما يحمل هذا الشعر من صور تتستر وراءها, في الأغلب الأعم, شخصيةُ الشاعر, وما تختزن هذه الصور بين عناصرها من نظرات تأملية تنبئ بالعِبر التي تعدّ محصلة تجارب ذاتية, وخبرات خبرها الشاعر في هذه الحياة. ولشعر الموالي خصوصية تتأتى من طبيعة الحياة التي عاشتها تلك الطبقة, والتي فرضتها ظروف الولاء والتبعية, وانطلاقاً من رغبتنا في الكشف عن علاقة الشعراء الموالي بدهرهم, فإننا سنتوسل بصورة الدهر في أشعار تلك الفئة, لعلها ترشدنا إلى تلك العلاقة, وتخبرنا بردة فعلهم تجاه الزمان وتبدله من جهة, وتجاه ما خلّفه دهرهم من مشكلات اجتماعية ونفسية في حياة أبناء تلك الطبقة الحادثة في المجتمع الأموي من جهة ثانية. Poetic texts, in general, give us access to the poet’s intimate environment and enable us to approach his reality, because they contain images, mostly concealing the poet’s personality and reflecting, through their varied aspects, contemplations, that convey messages drawn from the personal and public experiences encountered during the poet’s life . The uniqueness of the Mawaly poetry is attributed to the life-style they experienced as a social class, brought about by loyalty and subordination. Given that the objective of this paper is to explore the Mawaly poet’s attitude towards time, an attempt is being made to shed light on this attitude and discover their reaction against time and its fluctuations on the one hand as well as the socio-psychological problems that time had imposed upon members of this nascent class in Ummayyad society on the other.